Evaluation of otoscopy simulation as a training tool for real-time remote otoscopy. - Venail, Frederic; Akkari, Mohamed; Merklen, Fanny; Samson, Jacques; Falinower, Sylvain; Cizeron, Gilles; Mondain, Michel; Puel, Jean-Luc; Mura, Thibault (International Journal of Audiology, 2018)
Objective: Teleotoscopy requires the assistance of telehealth facilitators; but their training requirements remain to be determined. We evaluated the use of an otoscopy simulator to train facilitators to remote otoscopies sent via the Internet using a teleaudiology platform. Design: Neurotologists experts were asked to identify images using the otoscopy simulator and to perform an identification task of significant anatomical landmarks. The experts were asked to repeat those tasks remotely, with the help of facilitators who either received basic training, or no training prior to the experiment. Study sample: Three experts, three trained facilitators and three untrained facilitators participated in this study. Results: The use of an otoscopy simulator in addition to remote otoscopy yielded a good inter- and intrarater agreement (κ between 0.81-1, and 0.80-0.87, respectively). The accuracy of diagnosis was high on-site (11.7% error) and remotely (0% error). The time required for landmark identification task was not increased when performed remotely with a trained facilitator versus on-site otoscopy (9.3 versus 9.2 s/landmark). Conversely, the lack of training of facilitators increased significantly this time (15.6 s/landmark, p < 0.001). Conclusion: An otoscopic simulator coupled to teleaudiology software can be used to efficiently train both experts and facilitators to perform remote otoscopy.